Photovoltaic Projects for Multidimensional Poverty Alleviation: Bibliometric Analysis and State of the Art - Castro, Leonarda F. C.; Carvalho, Paulo C. M.; Saraiva, João P. T.; Fidalgo, José Nuno (International Journal of Energy Economics and Policy, 2024)
Motivated by initiatives such as the UN Sustainable Development Goals (SDG), particularly SDG 1 - Poverty Eradication and SDG 7 - Clean and Accessible Energy, the search for solutions aiming to mitigate poverty has been recurrent in several studies. This paper main objective is to evaluate the dynamics of global research on the use of photovoltaic projects for poverty alleviation (PVPA) from 2003 to 2022. We use a bibliometric analysis to identify publication patterns and consequently list research trends and gaps of the area. A total of 336 publications from Scopus database are identified and complemented by a state-of-the-art study, where the articles are investigated and classified according to: business model and financing and evaluation of PVPA results. The results show that PA is often associated with PV power and its application in rural areas. “Biomass” and “application in developing countries” have become a trend. Urban areas application, aiming to reduce poverty, and the need for a synergetic integration of energy and urban planning, to mitigate the risks associated with energy flow and efficiency, are the most relevant gaps identified. Most of the publications focus on macropolicies effects involving PV technology; papers on projects construction and ex-post are not identified.